Metamaterial-based UWB antenna - Pandey G.K.; Singh H.S.; Bharti P.K.; Meshram M.K. (My University, 2025)
A metamaterial-based novel compact microstrip antenna is presented for ultra-wideband (UWB) applications. The antenna consists of two layers of metamaterials made by etching a π-shaped slot and crossed-shaped slots, on the radiating patch and the ground plane, respectively. The series capacitance and shunt inductance developed due to the patterned radiating patch and ground plane lead to the left-handed behaviour of the metamaterial. The proposed antenna has a compact size of 30.8 × 27.6 × 0.8 mm3 and is fed by a 50 Ω microstrip line. The impedance bandwidth (-10 dB) is from 3 GHz to more than 14 GHz with maximum radiation in the horizontal plane and tends towards a directional pattern as the frequency increases. © The Institution of Engineering and Technology 2014.